TRANSFORMASI PENDAPATAN PBB MENJADI MODAL PEMBANGUNAN LOKAL: KAJIAN PUSTAKA TENTANG ALOKASI, AKUNTABILITAS, DAN DAMPAK PBB TERHADAP PELAYANAN PUBLIK DI PEMERINTAH DAERAH - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2026)
This article examines the transformation of Land and Building Tax (PBB) revenue into local development capital through an analysis of allocation, accountability, and its impact on public services in Indonesian local governments. Using a systematic literature review approach, this study found that the transfer of PBB-P2 since 2014 (90% to local governments) increased local revenue (PAD) in 96.5% of local governments, with collection effectiveness reaching 98% in developed regions such as DKI Jakarta. Best practices in e-PBB and SIMDA digitalisation have proven to strengthen fiscal transparency, although disparities in human resource capacity and weak organisational commitment remain major obstacles to accountability. Empirical impacts show that PBB contributions (19.64–69.7% of PAD) have a significant positive effect on HDI, infrastructure, education, and health through sectoral spending, with a strong correlation in local economic growth in Jombang and Batang. This study concludes that the integration of regulations, technology, and public participation is essential for optimising PBB as an instrument of sustainable regional autonomy. Policy implications include the replication of national e-budgeting, progressive NJOP reform, and human resource training through DJP-local government synergy. Further research is recommended using a panel regression model to measure the causality of PBB on SDGs in more than 500 local governments.